Internal Locus of Control and Self-Concept as Factors Affecting the Career Maturity of High School Students - Munawir Munawir; A. Muri Yusuf; Z. Mawardi Effendi; Afdal Afdal (International Journal of Research in Counseling and Education, 2018)
Determining the choice of jobs or education choices is one of the tasks during the development of the senior high school. For that, high school students are required to understand and master the concepts of career maturity to be able to pick and choose the appropriate career direction. Career maturity is influenced by several factors, including internal locus of control and self-concept. Someone who has an internal locus of control has a perception that the measures themselves would produce a positive thing that makes their work more successful. The self-concept is considered critical to the success of life because when someone feels good about himself and his ability, to predict a person's life will be successful.